2015
DOI: 10.1080/07448481.2014.983926
|View full text |Cite
|
Sign up to set email alerts
|

Napping in College Students and Its Relationship With Nighttime Sleep

Abstract: College students who are self-reported frequent, long, and late nappers may have a higher risk of poor nighttime sleep quality and more severe sleep deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…Epidemiological studies show similarly high levels of sleep disturbance among young people in general, and university students in particular. In a community-based random sample of young adults (aged 18–29 years), for example, Wong and Fielding [85] report 34% scoring >5 on the PSQI, while both Lund et al [86] and Ye et al [87] found that 60% of university students were similarly classified by the PSQI as poor sleepers. Given such findings, the expectation, a priori, reflected in the sports science literature that “…poor sleep quality would not be likely in a young, healthy athletic population” [67] is not supported by the epidemiological evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies show similarly high levels of sleep disturbance among young people in general, and university students in particular. In a community-based random sample of young adults (aged 18–29 years), for example, Wong and Fielding [85] report 34% scoring >5 on the PSQI, while both Lund et al [86] and Ye et al [87] found that 60% of university students were similarly classified by the PSQI as poor sleepers. Given such findings, the expectation, a priori, reflected in the sports science literature that “…poor sleep quality would not be likely in a young, healthy athletic population” [67] is not supported by the epidemiological evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos revelaram que o sono insuficiente, as saídas noturnas e a qualidade do sono influenciavam o desempenho académico de estudantes universitários (Gomes, Tavares, & Pinto de Azevedo, 2011), observando-se diferenças por sexo quanto aos horários de sono-vigília (Gomes, Tavares, & Pinto de Azevedo, 2009), e que os estudantes universitários a estudar fora da sua área de residência, também apresentavam horários de sono-vigília mais tardios durante a semana (Gomes, Tavares, & Pinto de Azevedo, 2008). A qualidade do sono parece ser afetada pelo facto de os estudantes do ensino superior manterem maus hábitos de sono frequentes (e.g., deitarem-se tarde ou privarem-se de sono (Ye, Hutton Johnson, Keane, Manasia, & Gregas, 2015). Acresce que a sonolência diurna se associa à qualidade e quantidade de sono, afetando a saúde geral dos estudantes (i.e., problemas físicos e mentais) ( Rose et al, 2015).…”
Section: Introductionunclassified
“…As Kloss et al (2015) mentioned, "emotions, physical well-being, and cognition could be negatively impacted by a lack of sleep" (p. 1). Ye et al (2015), discovered that "sleep deprivation and irregular sleep schedules, can lead to significant emotional imbalance, fatigue, poor concentration, impaired memory, and generally lower life satisfaction" (p. 88).…”
Section: Discussionmentioning
confidence: 99%
“…Students need to be more aware of how sleep affects their lifestyle. Ye, Johnson, Keane, Manasia, and Gregas (2015) found that periods of disturbed sleep or lack of sleep were caused by daytime napping. Students, who frequently took longer daytime naps, had decreased drive and attitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation